Challenges and coping experiences faced by nursing staff in long-term care facilities in China: a qualitative meta-analysis - Zhang, Shibo; Xiao, Xixi; Ai, Yating; Zhang, Ailin; Zhou, Chunyi; Hu, Hui; Wang, Yuncui (Frontiers in Public Health, 2024)
Objective The aim of this study is to discern the challenges and coping experiences encountered by nursing staff in long-term care facilities in China. This will be achieved through the identification, evaluation, and qualitative synthesis of comprehensive data. Design This is a qualitative meta-analysis. Methods The research systematically examined relevant literature sourced from six databases, concluding the search in August 2023. The inclusion criteria encompassed qualitative and mixed-methods studies in both Chinese and English, focusing on challenges faced by nursing staff in long-term care facilities and their corresponding coping strategies. The application of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework facilitated the qualitative meta-integration process. Three independent researchers meticulously screened and assessed the quality of the chosen studies. The synthesis process sought to amalgamate and structure analogous findings into novel categories through multiple readings of the original literature. These categories were subsequently distilled into comprehensive themes. Results Analyzed 15 articles revealed 14 sub-themes and 4 overarching analytical themes. These encompassed Sources of Challenges such as multitasking, clinical emergencies, workplace conflict, demand exceeding resources, and occupational discrimination. Psychological impacts included suppressed emotion, compassion fatigue, and self-doubt. Practical consequences involved damaged health, imbalanced life, and occupational disappointment. Coping strategies identified were self-adjusting, feeling validation and belonging, and finding support. Conclusion Our research identified the challenges faced by nursing staff in Chinese long-term care facilities and their coping experiences. We found that most challenges could be mitigated through appropriate adjustments in managerial strategies, such as reasonable human resources planning, and providing resource support, including material, emotional, and informational support. Similarly, institutions should have offered necessary emotional and psychological support to nursing staff to overcome the negative impacts of challenges and encourage them to adopt positive coping strategies.